2020
DOI: 10.1111/aos.14598
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvascular complexity comparing mono‐ and multifractal dimensions in relation to cardiometabolic risk factors in a Middle Eastern population

Abstract: Metrics that capture changes in the retinal microvascular structure are relevant in the context of cardiometabolic disease development. The microvascular topology is typically quantified using monofractals, although it obeys more complex multifractal rules. We study mono-and multifractals of the retinal microvasculature in relation to cardiometabolic factors. Methods: The cross-sectional retrospective study used data from 3000 Middle Eastern participants in the Qatar Biobank. A total of 2333 fundus images (78%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…As a proof of concept, our present study shows that all measured variables except lacunarity dimension were significantly lower in older group of participants confirming that complexity of microvascular network decreases with the age (Table 6 and Fig 4), which is in agreement with findings of other researchers [1,[20][21][22]. In these studies, age was associated with microvascular complexity measured by fractal dimension independent of other variables.…”
Section: The Proof Of the Conceptsupporting
confidence: 92%
See 2 more Smart Citations
“…As a proof of concept, our present study shows that all measured variables except lacunarity dimension were significantly lower in older group of participants confirming that complexity of microvascular network decreases with the age (Table 6 and Fig 4), which is in agreement with findings of other researchers [1,[20][21][22]. In these studies, age was associated with microvascular complexity measured by fractal dimension independent of other variables.…”
Section: The Proof Of the Conceptsupporting
confidence: 92%
“…As a proof of the concept, a smaller set of 10 color digital fundus images from healthy older participants was also included. The 82 retinal images were used to show that differences in age, gender, body mass index (BMI), alcohol, and tobacco use among the participants translate to changes in retinal microvascular patterns, and that the observed changes are similar to those already described by others [1,[20][21][22].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, they showed variability in fractal outcomes in different studies which was attributed to differences in populations studied, the equipment used to capture retinal images and segmentation tools used to define and calculate the fractals [ 50 ]. We have recently shown that retinal vessel multifractals are associated with glucose, hypertension and the WHO/ISH cardiovascular risk score [ 31 ] and that retinal vessel analysis is uniquely associated with blood pressure, glycemic status and obesity [ 51 ]. The current data suggests that the differences in retinal vessel fractals in patients with acute ischemic stroke may be further related to the pial collateral status.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the generalized dimensions (D q ) for q = 0, 1, and 2, which are the capacity dimension (D 0 ), which captures how much the data fills the physical space and provides global information about the structure; the information dimension (D 1 ), which captures the data density and quantifies the degree of disorder in the distribution; and correlation dimension (D 2 ), which measures how scattered the data is with a higher value indicating more compact data. For a multifractal structure, the following applies: D 0 ≥D 1 ≥D 2 [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%